The retropubic tension‐free vaginal tape procedure—Efficacy, risk factors for recurrence and long‐term safety. (14th February 2019) - Holdø, Bjørn; Verelst, Margareta; Svenningsen, Rune; Milsom, Ian; Skjeldestad, Finn E.
Abstract: Introduction: The retropubic tension‐free vaginal tape has been the preferred method for primary surgical treatment of stress urinary incontinence and stress‐dominated mixed urinary incontinence in women for more than 20 years. This study presents long‐term safety and efficacy data and assesses risk factors for long‐term recurrence. Material and methods: In a case‐series design we assessed a historical cohort of primary surgeries performed with the tension‐free vaginal tape procedure in 596 women from 1998 to 2012 with follow up through 2015. Information from the medical records was transferred to a case report form comprising data on early and late complications and recurrence of urinary incontinence defined as bothersome stress urinary incontinence symptoms. All analyses were performed with SPSS using Pearson chi‐square, survival and Cox regression analyses. Results: After a 10‐year follow up, mixed urinary incontinent women (hazard ratio 2.1, 95% confidence interval [CI] 1.4‐3.0) had a significantly increased risk of recurrence of stress urinary incontinence symptoms compared with women with pure stress urinary incontinence as the indication for surgery. Overall cumulative cure rates after 1, 5 and 10 years were 92% (95% CI; 90%‐94%), 79% (95% CI; 75%‐83%) and 69% (95% CI; 63%‐75%), respectively. Recurrent surgery (0.3%) and serious tape complications needing major surgical treatment (0.3%) were rare. Six patients (1.0%) had the tape cut due to urinary retention, and nine patients (1.5%) reported urinary retention more than 3 months after surgery. Conclusions: The tension‐free vaginal tape procedure has a high long‐term durability. Mixed urinary incontinence as an indication for surgery predicted long‐term recurrence. Long‐term complications were rare.